Dissemination and evolution of blaOXA-23 gene among carbapenem-resistant Acinetobacter baumannii isolates from central China - Xiaobing Guo; Zaiqiu Cao; Zhijian Zhang (Journal of Infection in Developing Countries)
This item has no abstract. Follow the links below to access the full text.